Implementation Of MBKM In Integrated Islamic High School Of Ternate City; Science And Social Synergy To Create A Superior Generation - Gafur, Harun; Yamin, Fahrun; Mustafa, Irfandi R. Hi (Universitas Cokroaminoto Yogyakarta, 2025)
This study aims to explore the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) program in the Integrated Islamic High School environment in Ternate City and its impact on strengthening synergy between science and social fields in forming a superior generation. The approach used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the application of the MBKM principle at the high school level, although still in the adaptation stage, has encouraged cross-disciplinary collaboration through problem-based learning projects and contextual learning. Students are given space to develop their potential holistically, both in academic and character aspects. Collaboration between science and social teachers is key to integrating Islamic values with a scientific and humanistic approach. The conclusion of this study states that the implementation of MBKM at the Integrated Islamic High School in Ternate City makes a significant contribution to efforts to produce a superior generation intellectually, spiritually, and socially.